Project-Based Learning to Improve Students’ Writing Skills in Narrative Story - Arif, Dara Nabila; Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to enhance the writing skills of eighth-grade students at SMP Negeri 1 Sikur, West Nusa Tenggara, through project-based learning (PjBL). Observations revealed difficulties in content, organization, language use, vocabulary, and mechanics. Using a classroom action research method across two cycles, data were collected through qualitative (observations and interviews) and quantitative (pre- and post-test writing assessments) approaches. The findings indicate significant improvements in students’ writing skills, including content (47%), organization (68%), vocabulary (68%), language use (53%), and mechanics (53%). These results demonstrate that PjBL effectively boosts writing performance by fostering active student involvement and peer feedback, highlighting its potential for improving writing skills in educational settings